The Fifth Generation Fixed Network (F5G): Full-Fiber Access Embracing the Gigabit Era - Sah, Chandra Bhushan; Shastri, Prabha; Dawadi, Babu R. (Advances in Engineering and Technology: An International Journal, 2022)
The rapid rise of the digital economy is aided by the new generation of information networks. Optical Fiber networks are foundation stone of cost-effective sustainable mode of communication of our society by leveraging high bandwidth, low latency, reliability, security, stability, enabling long-term economic growth through cutting-edge services and applications for industries, business and users. F5G intends to lay the groundwork for a systematic structure to the growth of fixed networks, including generational planning and pushing the technology's innovations and expansion into as many industries as feasible through Fiber-To-The-Everywhere-and-Everything. Fixed networks have become a crucial public infrastructure in the growing global digitization process, and their development level is an essential metric for evaluating a country's overall strength. This article introduces the trend for F5G networks along with recommendations for their development.